Seismic ambient noise - Fichtner, Andreas 1979-; Gualtieri, Lucia 1986-; Nakata, Nori 1984- (Cambridge University Press, 2019)
The seismic ambient field allows us to study interactions between the atmosphere, the oceans and the solid Earth. The theoretical understanding of seismic ambient noise has improved substantially in the last decades, and the number of its applications has increased dramatically. With chapters written by eminent scientists from the field, this book covers a range of topics including ambient noise observations, generation models of their physical origins, numerical modelling and processing methods. The later chapters focus on applications in imaging and monitoring the internal structure of the Earth, including interferometry for time-dependant imaging and tomography. This volume thus provides a comprehensive overview of this cutting-edge discipline for graduate students studying geophysics and for scientists working in seismology and other imaging sciences.